The optimal subsidy on electric vehicles in a metropolitan area - a SCGE study for Germany - Georg Hirte; Stefan Tscharaktschiew (European Regional Science Association (ERSA), 2012)
Many governments subsidize electric mobility (E-mobility) to increase the share of electric vehicles (EV) in the car fleet. This aims at reducing carbon emissions. Despite that there is not much research on the full economic costs and benefits of this measures. There are only a few Cost Benefit Analyses (CBA). They, however, do not take into account repercussion and substitution effects. We fill this gap in the literature and examine subsidies to EVs in a full spatial general equilibrium model. Since cities are the main area were EVs will be used, we focus on cities and apply a spatial approach. In particular, we ask whether it is optimal to subsidize or tax electric vehicles and, how large, the corresponding optimal rate is. We, first, derive analytically the optimal subsidy in a spatial partial equilibrium model of a city with two zones where commuting, carbon emissions, endogenous labor supply, fuel and power taxes are considered and where we distinguish between fuel vehicles and electric vehicles. There we find that the optimal subsidy rate is the sum of changes in externality costs (emissions + congestion), an opposite tax interaction effect, a redistribution effect between cities inhabitants and absentee landlords and a cost effect due to higher costs of producing travelling with power in comparison to fuel. The latter two effects are usually not considered in CBAs. Second, we extend the model to a full spatial general equilibrium model and employ simulations to calculate sign and size of the optimal subsidy or tax rate. This model is calibrated to a typical German metropolitan area. The results show that electric vehicles should not be subsidized but taxed. The results are robust with respect to changes in the willingness to adopt electric vehicles (EVs), changes in fix costs of EVs, and even if emission of EVs are zero. We change all these parameters to capture extreme and very unlikely behavior such as a very high demand elasticity of EVs with respect to the power tax rate, very low costs and the case that EVs have zero CO2 emissions. Concerning these variables we suggest that EVs should not be subsidized because welfare costs of achieving a small reduction in emissions are very high. We draw the conclusion that E-mobility might only be an efficient policy if it is considered as complement to other policies. This issue is left for future research.
Keywords: 330